The Role of Acupressure in Labor Pain Management: A Comprehensive Analysis of Efficacy and Maternal Outcomes - Meng Zhang; Yu Wang; Huixian Zhou; Siyuan Song; Jie Mu (Clinical and Experimental Obstetrics & Gynecology)
Objectives: Labor pain management is a critical aspect of maternal care, with methods broadly classified as pharmacological and non-pharmacological. While pharmacological approaches such as epidural anesthesia offer effective pain relief, they may prolong labor and lead to other complications. Acupressure, rooted in traditional Chinese medicine, presents a non-invasive alternative that alleviates anxiety, enhances maternal cooperation, and potentially expedites labor, albeit with limited analgesic efficacy. Mechanism: This comprehensive review analyzed studies on the use of acupressure for labor pain management, evaluating its effectiveness, mechanism of action, and impact on maternal and neonatal outcomes. Findings in brief: Acupressure was associated with a significant reduction in labor pain, with visual analog scale (VAS) scores decreasing by approximately 2 points compared to control groups. Acupressure also shortened labor duration by an average of 50 and 15 minutes in the first and second stages, respectively, improved maternal satisfaction (85% of women reported greater comfort), and, in some studies, reduced cesarean section rates. Mechanistically, acupressure alleviates pain through the gate control theory, stimulation of endogenous opioid release, and modulation of pain-related brain regions, such as the anterior cingulate cortex and insula. However, the analgesic effects of acupressure were found to be incomplete and reliant on accurate acupoint identification. Conclusions: Acupressure is a safe, accessible, and effective complementary method for labor pain management with additional benefits for maternal satisfaction and neonatal outcomes. While not a full substitute for pharmacological analgesia, integrating acupressure into clinical practice could provide a holistic approach to labor care. Future research should focus on standardizing methodologies and exploring their application in diverse populations.